Perceptions of police use of force: the importance of trust. Issue 1 (23rd November 2020) - Kyprianides, Arabella; Yesberg, Julia A.; Milani, Jenna; Bradford, Ben; Quinton, Paul; Clark–Darby, Oliver
Abstract : Purpose: The range of tactical force options available to police is increasing, while public debate about police use of force is never far from the headlines. This paper aims to examine what factors shape how people accept police use of force. Design/methodology/approach: The authors use two online experiments to test whether different force options affected judgments about the acceptability of police action and to explore the role of trust and legitimacy in people's judgments. Findings: The authors found across both studies that respondents judged scenarios involving a weapon (baton, CS spray, Taser) as less acceptable compared to scenarios that did not (talking down, handcuffs), but they did not draw much distinction between the specific weapon used. In study 1, exposure to different police tactics had no effect on trust and legitimacy. In study 2, prior perceptions of trust were strong predictors of acceptability judgments. Originality/value: There is a comparative paucity of British-based empirical research examining public attitudes toward different use of force resolutions by police. In this paper, the authors explore how use of force affects people's views of police at a time in which the nature and scope of force applications, how these are understood and indeed the basic enterprise of policing itself is being reconsidered and renegotiated.